Assuming n is a positive integer, evaluate the following integral:
∫ 0 ∞ e t t n d t
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Typo in line 1: d t , not d x .
How are you so good in calculus and higher math at 14??
Log in to reply
There are many people like that. It al is on dedication. If you have loved maths from a young age,you would strive to achieve further in it.
I will prove this theorem by induction.
Base case ( n = 0 ): ∫ 0 ∞ t 0 e − t d t = − e − t ∣ ∣ ∣ 0 ∞ = − ( 0 − 1 ) = 1 = 0 !
Induction step: Assume ∫ 0 ∞ t n e − t d t = n ! .
I now show ∫ 0 ∞ t n + 1 e − t d t = ( n + 1 ) ! .
∫ 0 ∞ t n + 1 e − t d t = − t n + 1 e − t ∣ ∣ ∣ 0 ∞ + ∫ 0 ∞ ( n + 1 ) t n e − t d t = 0 + ( n + 1 ) n ! = ( n + 1 ) ! .
By the principle of mathematical induction, ∫ 0 ∞ t n e − t d t = n ! for all n ≥ 0 .
Problem Loading...
Note Loading...
Set Loading...
The integral ∫ 0 ∞ e t t n d t
can be written as ∫ 0 ∞ t n + 1 − 1 e − t d t = Γ ( n + 1 )
& as n is an positive integer Γ ( n + 1 ) = ( n ) !